2016
DOI: 10.1186/s40064-016-3608-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diets with different energy concentrations on growth performance, carcass characteristics and meat chemical composition of broiler chickens in dry tropics

Abstract: Background Diets with increasing levels of energy were fed for 42 days to 200, 1-day old male broiler chickens to evaluate growth performance, carcass characteristics and chemical composition of meat. The study was performed in the subtropical area of northeastern Mexico. Treatments diets (T) for starter and finisher phases had apparent metabolizable energy (AME; kcal/kg) of: 2960 and 3040 (T1); 3000 and 3080 (T2); 3040 and 3120 (T3); 3080 and 3160 (T4), respectively. Within each of the growing phases the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 15 publications
11
16
1
1
Order By: Relevance
“…(2017). A similar result was found by Infante-Rodríguez et al (2016) when evaluating rations with increasing levels of metabolisable energy in the 1 to 21-day phase (2960, 3000, 3040, and 3080 Kcal kg -1 of feed) who verified a better FC for broilers fed the diets containing the highest energy levels.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…(2017). A similar result was found by Infante-Rodríguez et al (2016) when evaluating rations with increasing levels of metabolisable energy in the 1 to 21-day phase (2960, 3000, 3040, and 3080 Kcal kg -1 of feed) who verified a better FC for broilers fed the diets containing the highest energy levels.…”
Section: Resultssupporting
confidence: 83%
“…Considering the integral period evaluated (37 days), similar to the present experiment, Infante-Rodríguez et al (2016) verified an improvement in the FC of birds fed with higher energy rations. In agreement, Nogueira et al (2013) observed an increase in weight gain and an improvement in feed conversion by birds in response to increased feed energy levels.…”
Section: Concomitantsupporting
confidence: 88%
“…However, the percentage of breast meat yield was not affected by diet in the present experiment. Similar results have been reported previously by van Nguyen and Bunchasak (2005) and Infante-Rodr ıguez et al (2016). On the other hand, the percentage of breast meat yield was decreased in the heat stressed birds.…”
Section: Discussionsupporting
confidence: 92%
“…Resultados similares fueron obtenidos por Sugeta et al (13); Morais et al (16) y Urdaneta-Rincón y Leeson, (43), razón por la cual la estrategia de supresión alimenticia aplicada en el presente estudio no ejerció ningún efecto negativo sobre la ganancia de peso, lo que sugiere una compensación favorable del crecimiento. En cuanto al CA, este fue ligeramente superior en los animales alimentados ad libitum, registrándose un valor promedio total de 4181.01 ± 306.46 g entre tratamientos, muy similar al calculado por Henn et al (37); Mendes et al (44), e InfanteRodríguez et al (45). Sahraei (12) afirma que la tasa de crecimiento está relacionada con el CA, por lo que la restricción alimenticia podría inhibir considerablemente la GTP; sin embargo, el análisis estadístico arrojó que el CA registrado en el T 3 y T 4 , fue significativamente menor (p < 0.05) con respecto al grupo control, en tal sentido, los criterios prácticos de análisis productivo empleados actualmente por los avicultores, sugieren que el valor calculado de CA en el T 4, probablemente ejerce un impacto económico significativo, considerando que la alimentación constituye el costo variable más alto (46).…”
Section: Análisis Estadísticounclassified